Phosphate Solubilizing Microorganisms 2014
DOI: 10.1007/978-3-319-08216-5_5
|View full text |Cite
|
Sign up to set email alerts
|

Cold-Tolerant Phosphate-Solubilizing Microorganisms and Agriculture Development in Mountainous Regions of the World

Abstract: In many mountainous regions of the world, agriculture faces several major challenges. Of these, cold temperatures and low fertility of soils are of particular importance. For instance, in the Indian Himalayas and in the High Andes, soils are acidic and phosphorus deficient, severely limiting crop production. In the contemporary world, the use of biofertilizers-especially nitrogen fixers and phosphate solubilizers-to enhance crop yields has become an attractive alternative for farmers, due to low costs and no e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 93 publications
0
3
0
Order By: Relevance
“…The usefulness of such bacterial strains in cold-adapted agroecosystems (e.g., hill and mountain) seems huge due to the exceptional crop-raising conditions and the environmental situations of the high altitude agricultural systems [165,166]. The cold-adapted P biofertilizers could resist/tolerate the extremities of cold and maintain their functional qualities even under cold environments [167]. Considering the vast and varied plant growth-promoting potentials, the application of indigenous phosphate biofertilizers in cold soils can be a central approach to preserve soil fertility, protect microbial diversity, and concomitantly optimize crop production more sustainably.…”
Section: Importance Of P and Rationale For Using Cold-active Bacterial Phosphate Biofertilizers In Low-temperature Environmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The usefulness of such bacterial strains in cold-adapted agroecosystems (e.g., hill and mountain) seems huge due to the exceptional crop-raising conditions and the environmental situations of the high altitude agricultural systems [165,166]. The cold-adapted P biofertilizers could resist/tolerate the extremities of cold and maintain their functional qualities even under cold environments [167]. Considering the vast and varied plant growth-promoting potentials, the application of indigenous phosphate biofertilizers in cold soils can be a central approach to preserve soil fertility, protect microbial diversity, and concomitantly optimize crop production more sustainably.…”
Section: Importance Of P and Rationale For Using Cold-active Bacterial Phosphate Biofertilizers In Low-temperature Environmentsmentioning
confidence: 99%
“…Since the solubilization of inorganic P largely depends on the membrane-bound enzymes, the low temperatures may intensely affect its efficacy under a mesophilic environment. So, such conventional PSB requires urgent bioprospecting especially for solubilizing enzymes so that they remain active and perform efficiently at low temperatures, like those performed by cold-active PSB [167]. The OA secreted either by cold-active PSB or conventional PSB into the culture supernatant can be detected by paper or TLC [182] or by HPLC [20,183].…”
Section: Mechanisms Of P-solubilization In Cold-adapted Bacteria: An Overviewmentioning
confidence: 99%
“…PGPBs natives to alpine systems are essential nowadays due to their ability to cope with low temperatures and to promote plant growth through different mechanisms under cold conditions and poor nutrient soils ( Chaturvedi and Shivaji, 2006 ; Jaggi et al, 2020 ; Farooq et al, 2022 ). These constraint conditions for plants can be alleviated by PGPBs through the activity of enzymes and phytohormones that favor plant nutrient uptake and stress resistance ( Haselwandter et al, 1983 ; Widawati and Suliasih, 2006 ; Joshi et al, 2014 ; Yarzábal, 2014 ; Kadioglu et al, 2018 ; Pandey and Yarzábal, 2019 ; Fan et al, 2021 ). Some studies have reported PGPBs in alpine ecosystems ( Yadav et al, 2015 ), described their diversity in terms of factors structuring bacterial communities ( Tang et al, 2020 ; Wang et al, 2020 ; Rui et al, 2022 ), and quantified their plant growth-promoting activity ( Haselwandter et al, 1983 ; Widawati and Suliasih, 2006 ; Viruel et al, 2011 ; Yadav et al, 2015 ; Kadioglu et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%